Hypoxia and Foxn1 alter the proteomic signature of dermal fibroblasts to redirect scarless wound healing to scar-forming skin wound healing in Foxn1−/− mice - Gawronska-Kozak, Barbara; Machcinska-Zielinska, Sylwia; Walendzik, Katarzyna; Kopcewicz, Marta; Pääkkönen, Mirva; Wisniewska, Joanna (BMC, 2025)
Background: Foxn1-/- deficient mice are a rare model of regenerative skin wound healing among mammals. In wounded skin, the transcription factor Foxn1 interacting with hypoxia-regulated factors affects re-epithelialization, epithelial-mesenchymal transition (EMT) and dermal white adipose tissue (dWAT) reestablishment and is thus a factor regulating scar-forming/reparative healing. Here, we hypothesized that transcriptional crosstalk between Foxn1 and Hif-1α controls the switch from scarless (regenerative) to scar-present (reparative) skin wound healing. To verify this hypothesis, we examined (i) the effect of hypoxia/normoxia and Foxn1 signalling on the proteomic signature of Foxn1-/- (regenerative) dermal fibroblasts (DFs) and then (ii) explored the effect of Hif-1α or Foxn1/Hif-1α introduced by a lentiviral (LV) delivery vector to injured skin of regenerative Foxn1-/- mice with particular attention to the remodelling phase of healing.
Results: We showed that hypoxic conditions and Foxn1 stimulation modified the proteome of Foxn1-/- DFs. Hypoxic conditions upregulated DF protein profiles, particularly those related to extracellular matrix (ECM) composition: plasminogen activator inhibitor-1 (Pai-1), Sdc4, Plod2, Plod1, Lox, Loxl2, Itga2, Vldlr, Ftl1, Vegfa, Hmox1, Fth1, and F3. We found that Pai-1 was stimulated by hypoxic conditions in regenerative Foxn1-/- DFs but was released by DFs to the culture media exclusively upon hypoxia and Foxn1 stimulation. We also found higher levels of Pai-1 protein in DFs isolated from Foxn1+/+ mice (reparative/scar-forming) than in DFs isolated from Foxn1-/- (regenerative/scarless) mice and triggered by injury increase in Foxn1 and Pai-1 protein in the skin of mice with active Foxn1 (Foxn1+/+ mice). Then, we demonstrated that the introduction of Foxn1 and Hif-1α via lentiviral injection into the wounded skin of regenerative Foxn1-/- mice activates reparative/scar-forming healing by increasing the wounded skin area and decreasing hyaluronic acid deposition and the collagen type III to I ratio. We also identified a stimulatory effect of LV-Foxn1 + LV-Hif-1α injection in the wounded skin of Foxn1-/- mice on Pai-1 protein levels.
Conclusions: The present data highlight the effect of hypoxia and Foxn1 on the protein profile and functionality of regenerative Foxn1-/- DFs and demonstrate that the introduction of Foxn1 and Hif-1α into the wounded skin of regenerative Foxn1-/- mice activates reparative/scar-forming healing.
Keywords: Dermal fibroblasts; Foxn1; Hypoxia; Pai-1; Regeneration; Skin wound healing.